Leveraging Artificial Intelligence for Competitive Advantage in SMEs An Empirical Analysiss - Ferdiansyah, Januri; Abudaqa, Anas; Lansonia, April (APTISI Transactions on Management (ATM), 2025)
Small and Medium Enterprises (SMEs) face significant challenges in a com- petitive market. Artificial Intelligence (AI) has emerged as a critical tool for enhancing business operations, yet the specific impact of AI on the competi- tive advantage of SMEs remains underexplored. This study aims to investigate how AI adoption influences the competitive advantage of SMEs, focusing on key performance indicators such as cost efficiency, market share, customer retention, and innovation. The study adopts a quantitative research approach using Par- tial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. Data was collected from 200 SMEs across various industries that have implemented AI technologies. A survey was conducted to assess AI adoption and its impact on competitive advantage. The results indicate that AI adoption positively affects all four dimensions of competitive advantage. The strongest impact was observed on cost efficiency, followed by customer retention, inno- vation, and market share. The relationships between AI adoption and competi- tive advantage were statistically significant. AI adoption provides SMEs with a powerful means to enhance competitiveness by improving operational effi- ciency, customer loyalty, and innovation. Policymakers should support SMEs in overcoming adoption barriers to fully realize these benefits.